Impact Analysis of Forest and Peatland Landscape Change: Socio-Economic and Environmental Implications - Ishak, Andhika Agung Permana Ibnu (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
Background: Forest fires represent natural disasters that often stem from environmental conditions, including events like El Niño or extreme climatic situations. Rainfall, a crucial factor, plays a role in influencing extreme climate occurrences. Areas with high potential for forest fires encompass conservation zones closely linked to human activities. An illustrative example is the Bromo Tengger Semeru National Park (TNBTS), which serves both as a conservation and tourist area. The presence of human tourists or visitors in these conservation zones creates conditions conducive to forest fires, particularly when supported by extreme climatic conditions. Method: This study used field observation methods, satellite data analysis, and interviews with authorities and environmental experts. The data collected included the area affected, the plant types, and the environmental conditions after the fire. Findings: TNBTS experiences a specific rainfall pattern, with the lowest precipitation observed in May-Jun-Jul-Aug-Sept and the highest in Nov-Dec-Jan-Feb-Mar. During periods of low rainfall, TNBTS becomes susceptible to fires, necessitating preventative measures in the month leading up to the dry season. Initiating preventative actions at the onset of the dry season, notably in May, is crucial for controlling forest fires. Analyzing hotspot data of fire incidents from 2001 to 2020 reveals peak occurrences among other nationalities in 2001, 2014, and 2019. Identification based on data indicates that not all hotspots signify fire incidents; some result from heat emanating from Mount Semeru's crater at the TNBTS location. Conclusion: This article concludes the importance of cooperation between authorities, environmental organizations, and communities in forest fire prevention and recovery efforts in Bromo National Park. Novelty/Originality in this article: This study also offers a new perspective in the interpretation of hotspot data by distinguishing between forest fires and volcanic activity and identifying May as a critical period for initiating preventive action analysis based on long-term rainfall patterns.